2017
DOI: 10.1007/s11095-017-2132-4
|View full text |Cite
|
Sign up to set email alerts
|

High Penetration of Paclitaxel in Abdominal Wall of Rabbits after Hyperthermic Intraperitoneal Administration of Nab-Paclitaxel Compared to Standard Paclitaxel Formulation

Abstract: Our results show that nab-paclitaxel penetrates into the abdominal wall better than CRE-paclitaxel, in terms of effective penetration and peritoneal tissue concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Preliminary data from animal models seem to confirm the potential of IP ABP administration. Coccolini and coworkers compared HIPEC with either ABP or cremophor-based paclitaxel in a rabbit model and found that ABP penetrated up to 0.63 mm in the (healthy) peritoneal wall, while the standard formulation was not detectable in the peritoneum [8]. We have recently demonstrated that IP ABP results in significant antitumor efficacy in a mouse xenograft model of peritoneal metastasis from ovarian origin (Carlier et al, manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data from animal models seem to confirm the potential of IP ABP administration. Coccolini and coworkers compared HIPEC with either ABP or cremophor-based paclitaxel in a rabbit model and found that ABP penetrated up to 0.63 mm in the (healthy) peritoneal wall, while the standard formulation was not detectable in the peritoneum [8]. We have recently demonstrated that IP ABP results in significant antitumor efficacy in a mouse xenograft model of peritoneal metastasis from ovarian origin (Carlier et al, manuscript in preparation).…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies have demonstrated that IP administration of nano-and microsized formulations of paclitaxel results in superior antitumor activity against mouse ovarian cancer (OC) xenografts compared to intravenous administration [7]. In a recent study using an HIPEC model in the rabbit, peritoneal tissue concentrations after IP ABP were five times higher compared to IP Taxol [8]. IP catheter-based delivery of Abraxane was recently studied in a phase I clinical trial in advanced carcinomatosis patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Simulations based on population pharmacokinetic modeling showed that the tissue distribution of nab-PTX was more dependent upon an active transport mechanism, i.e., endothelial transcytosis for drug distribution into tissues than that of sb-PTX [8]. A preclinical study in rabbits, in which nab-PTX and sb-PTX were intraperitoneally administered, showed that nab-PTX penetrated the peritoneum tissue better than sb-PTX [9]. Moreover, a previous preclinical study that compared intravenous administration of nab-PTX with intraperitoneal administration of sb-PTX in a peritoneal metastasis mouse model reported that intravenous nab-PTX demonstrated an equivalent effect of reducing ascites and peritoneal tumors to intraperitoneal sb-PTX at equal doses [10].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its nature, the peritoneum is poorly reached by systemic chemotherapy due to the plasma-peritoneal barrier [ 2 3 4 5 ]. For these reasons intraperitoneal chemotherapy was introduced with promising results: the administration of drug directly into the peritoneal cavity allows an effective dose delivered to the tumor site without reaching plasma toxicity levels [ 4 6 7 8 ]. Moreover, chemotherapeutics could be delivered associated with hyperthermia (hyperthermic intraperitoneal chemotherapy [HIPEC]) increasing the effect of the drug with the heat [ 9 ].…”
Section: Introductionmentioning
confidence: 99%